(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2023)
The article discusses the evolution of herbarium aesthetics, from the first scientific drawings to the emergence of botanical photography and its relationship to artistic movements such as Art Nouveau. It highlights the impact of works such as Karl Blossfeldt’s on botanical photography and how these images marked a turning point in the representation of herbaria. A number of contemporary photographic projects are presented that reinterpret the classical aesthetic of the herbarium and question the relationship between the real and the simulated in the image. These examples illustrate a critical and socially engaged re-reading that proposes a new approach to the representation of nature. The article concludes by reflecting on the need to revise the conventional standards of herbaria, which have relegated plants to mere objects of study, stripping them of their context and cultural significance. It proposes a new look at botany, from both art and science, that recognises and respects the complexity and interdependence between plants and their environment, thus challenging the patriarchal view of the relationship between humans and nature.